2004
DOI: 10.1586/14789450.1.4.411
|View full text |Cite
|
Sign up to set email alerts
|

Depletion and fractionation technologies in plasma proteomic analysis

Abstract: This review intends to survey the traditional and current technologies in the depletion and subfractionation of plasma proteins for further analyses. The value of depletion aims to enrich low-abundant proteins by removing highly abundant proteins, such as albumin or immunoglobulin G, from plasma. With this approach, one can examine both the resulting high- and low-abundant protein fractions. The depleted protein population can be further subfractionated based on their isoelectric point ranges, creating a more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…Since, human plasma can be easily obtained, several laboratories have developed various proteomic strategies for the purpose of using plasma proteins as a source for possible disease-related biomarkers [7][8][9][10][11][12][13][14][15]22]. However, the great variety of protein types present, as well as the extended dynamic range of protein concentrations greatly hinders the identification of plasma biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Since, human plasma can be easily obtained, several laboratories have developed various proteomic strategies for the purpose of using plasma proteins as a source for possible disease-related biomarkers [7][8][9][10][11][12][13][14][15]22]. However, the great variety of protein types present, as well as the extended dynamic range of protein concentrations greatly hinders the identification of plasma biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…2). After focusing, the region below pH 4.8, which did not contain proteins, was excised, and the 12 cm trimmed IPG strip was separated in second dimension using gels of four different heights (8,12,15, and 19 cm). The numbers of spots detected in these gels were 1039 l 36, 1304 l 40, 1312 l 38, and 1327 l 40, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Several types of columns containing IgGs from different mammalian species (goat, mouse, rabbit, etc.) are commercially available [42]. Hinerfeld et al reported that chicken anti-human HSA immunoglobulin Y (IgY) antibodies -bound to hydrazide beads -featured high affinity towards human albumin, thus provided highly specific depletion [43].…”
Section: Affinity-based Depletion Of the High Abundant Plasma Proteinsmentioning
confidence: 99%